Antioxidants in food : practical applications - Yanishlieva, Nedyalka; Gordon, Michael H., 1949-; Pokorny, Jan, 1928- (Woodhead Publishing in food science and technology., 2001)
Antioxidants are an increasingly important ingredient in food processing, as they inhibit the development of oxidative rancidity in fat-based foods, particularly meat and dairy products and fried foods. Recent research suggests that they play a role in limiting cardiovascular disease and cancers. This book provides a review of the functional role of antioxidants and discusses how they can be effectively exploited by the food industry, focusing on naturally occurring antioxidants in response to the increasing consumer scepticism over synthetic ingredients.